Acute Arthrodesis of Ipsilateral Pilon and Talus Fracture: A Case Report. Issue 2 (April 2021) - Sanders, Drew
Abstract : Case: We report a unique case of an ipsilateral distal tibia pilon fracture and talar body after motor vehicle collision. Our patient was successfully treated with acute arthrodesis of the tibiotalar joint, with return to good function 1-year after surgery. Conclusion: Pilon and talus fractures are complex injuries. They require specialized surgical care, are complicated by loss of function, continued pain, and lead to subsequent reconstructive procedures such as arthrodesis or arthroplasty. In the presence of concomitant pilon and talus fractures, acute arthrodesis can yield good results and return to function.